VISTA expression and patient selection for immune-based anticancer therapy - Martin, Alexander S.; Molloy, Michael; Ugolkov, Andrey; von Roemeling, Reinhard W.; Noelle, Randolph J.; Lewis, Lionel D.; Johnson, Melissa; Radvanyi, Laszlo; Martell, Robert E. (Frontiers in Immunology, 2023)
V-domain Ig suppressor of T-cell activation (VISTA) is a B7 family member that plays key roles in maintaining T cell quiescence and regulation of myeloid cell populations, which together establish it as a novel immunotherapy target for solid tumors. Here we review the growing literature on VISTA expression in relation to various malignancies to better understand the role of VISTA and its interactions with both tumor cells and immune cells expressing other checkpoint molecules within the tumor microenvironment (TME). The biology of VISTA creates several mechanisms to maintain the TME, including supporting the function of myeloid-derived suppressor cells, regulating natural killer cell activation, supporting the survival of regulatory T cells, limiting antigen presentation on antigen-presenting cells and maintaining T cells in a quiescent state. Understanding these mechanisms is an important foundation of rational patient selection for anti-VISTA therapy. We provide a general framework to describe distinct patterns of VISTA expression in correlation with other known predictive immunotherapy biomarkers (programmed cell death ligand 1 and tumor-infiltrating lymphocytes) across solid tumors to facilitate investigation of the most efficacious TMEs for VISTA-targeted treatment as a single agent and/or in combination with anti-programmed death 1/anti-cytotoxic T lymphocyte antigen-4 therapies.